Zoological Nomenclature and Electronic Publication—a reply to Dubois et al. (2013) - Iczn, Iczn (Zootaxa, 2014)
A group of 19 authors (Dubois et al. 2013) recently raised concerns about the latest Amendment to the International Code of Zoological Nomenclature (ICZN 2012a,b,c), that allows new names and other nomenclatural acts to gain legislative acceptance (become “available”) from publications issued and distributed electronically. Two editorials by publishers have already responded to some of the concerns (Anonymous 2013, Harold et al. 2013); some others will be dealt with here.  Technological advances in electronic scientific communication have had a dramatic effect on scientific research and publication in recent years.  Addressing this, and following a four-year period of public discussion, the International Commission on Zoological Nomenclature (ICZN) voted to accept an Amendment to the 4th edition of the Code, thereby adapting the rules of zoological nomenclature to new realities of publication media and methods (ICZN 2012a,b,c). The Amendment dealt with the most important issues of publishing in an electronic world, but in all transitional times new regulatory guidelines may have difficulties keeping up with the rate of change. As mentioned by Harold et al. 2013, the “devil may be in the detail”, but it is a process that must nevertheless be started.  The ICZN encourages all interested individuals and groups to participate in the discussion leading up to the 5th edition of the International Code of Zoological Nomenclature, whether by the ICZN e-mail discussion list, the 5th edition Wiki, Bulletin of Zoological Nomenclature or through other media, to help make the next edition satisfy the needs of the community.